The relationship between community workers’ occupational stress, social support and psychological health: an empirical study in Liaoning Province, China - Sen, Qin; Lei, Zhang (Frontiers in Psychology, 2024)
Background With increasing urbanization in China, the community has assumed the important task of social governance and service provision, which has resulted in an increase in community workers’ occupational stress. To date, researchers have studied ways to improve community workers’ working ability, but have paid less attention to their health, especially their psychological health. This study examined the relationship between occupational stress, social support and community workers’ psychological health. Methods A total of 545 community workers from 14 cities in Liaoning Province completed a questionnaire including the Occupational Adaptability Scale for Employees (OASE), the Social Support Rating Scale (SSRS) and the SCL-90-R scale (a measure of psychological health). Correlational and regression analyses were conducted. Results Community workers’ occupational stress mainly derives from their workload, career development opportunities and performance appraisals. Participant’s psychological health scores were significantly negatively correlated with occupational stress and significantly positively correlated with social support. Social support plays a moderating effect in the relationship between community workers’ occupational stress and their psychological health. Conclusion It is necessary to establish an effective community support system, reduce the burden on the community, optimize existing work processes and performance appraisal system, create a positive working environment and organizational culture, and promote employee’s psychological health.